Functional outcome of surgical management of ankle fractures classified as per Lauge-Hansen classification - Mehta, Nisarg R.; Tijoriwala, Prabhav P.; Sidhdhapuria, Pratik V. (International Journal of Research in Orthopaedics, 2026)
Background: Ankle fractures are one of the common types of fractures treated by orthopaedic surgeons. There has been an increase in the prevalence of such fractures over the last two decades both in the young and active patients and in the elderly. The Lauge-Hansen classification system, based on the mechanism of injury, remains one of the most widely used methods for categorizing ankle fractures. It divides fractures into four main types-supination-adduction (SA), supination-external rotation (SER), pronation-abduction (PA), and pronation-external rotation (PER)-based on the position of the foot at time of injury and the direction of the applied force. Ankle injuries gain importance because the whole-body weight is transmitted through the ankle and locomotion depends upon the stability of the ankle joint Methods: The inclusion criterion included all those ankle fracture more than 18 years and who consent to participate. The operative procedure was performed within 4 to 5 days of the injury. A preoperative clinical examination of the affected ankle was carried in all aspects like- abrasions, swelling, contusion, puckering and neurovascular deficit. Antero posterior (AP) and lateral (Lat) and mortise radiographs of the patient were evaluated. Results: Out of the thirty patients followed up to a minimum of 18 months in the study twenty-one were males and nine were females. The mean age was 41.3 years (range 18 to>50 years). Eighteen out of thirty patients (60%) had the right side fractured and remaining twelve out of thirty had a left sided fracture (40%). In terms of anatomical classification trimalleollar fractures constituted the majority of cases (n=17,56.7%), followed by brimalleolar fractures (n=13, 43.3%). Five patients (16.7%) had open fractures classified as Gustilo-Anderson grade I or II, while the remaining 25 (83.3% presented with closed injuries. Conclusions: Surgical treatment of ankle fractures, guided by accurate classification and operative principles, leads to favorable outcomes. The Lauge-Hansen system remains useful for diagnosis, prognosis, and surgical planning. Further multicenter studies with extended follow-up are needed to optimize care for complex fracture types.